(untitled) (Journal of the College of Basic Education, 2022)
The first chapter includes the research problem and the need for it, determining the importance of the research and the beneficiaries of it, and defining the goal of the research, which is determined in revealing: The educational functions of psychodrama in school theater performances. The researcher also identified the basic terms covered by the research As for the second chapter, it was devoted to the theoretical framework of the research and the previous studies in it, as it included two topics, the first dealt with the psychedelic elements and its importance, while the second topic: the school theater, its importance and the educational functions of psychodrama in the school theatre. Determining some of the indicators that resulted from the theoretical framework and previous studies ,As for the third chapter, the researcher determined the research methodology and procedures and determined the research community, which includes (3) theatrical performances.To measure the goal of the research, the researcher discussed and described the scenes of a psychodrama tic character in each of the research samples, to reveal the achievement of the goals that were set for them, to reach the results, and by presenting the results, the researcher reached the most important conclusions and then the recommendations and suggestions made by the researcher.